f(x)= 2x + 1
f(-2)=2*(-2)+1
f(-2)=-4+1
f(-2)=-3
2007-01-02 15:10:52
·
answer #1
·
answered by yupchagee 7
·
15⤊
0⤋
2(-2)+1=-3
2007-01-02 15:12:52
·
answer #2
·
answered by James R, the seeker 1
·
1⤊
0⤋
*The x-variable represents a number/value. In this case, the problem gives you the number which, is -2 >
First: replace -2 with the x-variable >
f(-2)= 2(-2) + 1
f(-2) = - 4 + 1
f(-2)= -3
2007-01-02 15:17:56
·
answer #3
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
2(-2) +1
-4 + 1
= -3 is the answer when f(-2)
2007-01-02 15:06:24
·
answer #4
·
answered by michael45672007 3
·
1⤊
0⤋
to find value of f(-2), substitute -2 wherever there is an 'x'.
therefore, f(-2)
= 2(-2) + 1
= -4 + 1
= -3
2007-01-02 15:07:13
·
answer #5
·
answered by Anonymous
·
1⤊
0⤋
f(-2)=2(-2)+1
f(-2) =-4+1
f(-2) = -3
2007-01-02 15:22:19
·
answer #6
·
answered by daddyspanksalot 5
·
0⤊
0⤋
replacce all x with -2 and calculate the resulting sum
2007-01-02 16:05:56
·
answer #7
·
answered by gjmb1960 7
·
0⤊
0⤋
f(-2)=2(-2)+1
f(-2)= -4+1
f(-2)= -3
2007-01-02 15:06:14
·
answer #8
·
answered by 7
·
1⤊
0⤋
I did it a little different.
you have to have the same f(x)=2x+1x=3
2007-01-02 15:13:35
·
answer #9
·
answered by karen v 6
·
0⤊
1⤋
f(-2)=2(-2)+1
f(-2)=-4+1
f(-2)=-3
2007-01-02 15:12:20
·
answer #10
·
answered by marinescheerleader 2
·
1⤊
0⤋